Quality control study on Concrete Ventures Group, Inc. - Abarra, Geraldine; Baradas, Jennifer; De Jesus, Eleanor; Katigbak, Cristel (College of Engineering, 2001)
Concrete Ventures Group Incorporated (CVGI), the company under study, is a manufacturing company that deals with the manufacturing and marketing of pre-cast, pre-stressed reinforced concrete beams. Promoted under the brand name C-JOIST, C-joist 101 (one of the three types of C-Joists manufactured by CVGI) was the chosen product to be focused on mainly because it contributes 60 percent to the total sales of the company. The study is centered on documenting and analyzing product and process quality control and also on the improvement of the production processes and the attainment of proper control of quality characteristic drivers. Product, Process, Quality characteristics and control documentation were obtained through actual plant visits, interviews of key personnel, and review of the company's production. Problem identification tools learned in the Statistical Quality Control course were applied to be able to pinpoint and verify causes of the company's recurring problem, which is rejection of C-Joists. The identified quality characteristics dictating the rejection of a C-Joist 101 were (a) compressive strength below 6,000 psi; (b) flexural strength below 10,000 psi; and (c) the occurence of cracks. Utilizing techniques in statistical process control to compute for the control limits, the flexural and compressive characteristics as determined by the process shown to be out of control and the process is incapable. For cracks, the process was concluded to be in control however, it was shown to be incapable. Assignable causes were identified and thereafter analyzed and these were narrowed down to three : 1.) Proportion of water; 2) Percent sand by weight of total aggregates; 3.) Cutting time. Through brainstorming, study of the manufacturing process, and review of SPC tools and techniques, the group generated possible solutions or methods of improvement to address the assignable causes. Recommendations include regular measurement and recording of the water content of the aggregates before mixing, sieving of the sand upon delivery from the supplier, appropriate design of sampling plans for testing of compressive an flexural strengths, and corresponding forms for the testing that the company can use for the recommended measurement and sampling plans. A recommendation that is subject to further study is the determination of an optimal schedule for the curing of the C-Joist. The chosen alternatives are subjects for the implementation, where the group suggested some means in attaining and implementing those alternatives. These plans are guides for the subject company so that they may be able to implement the various changes brought about by the alternatives.